Great Barrier Reef World Heritage: Nature in Danger - Pocock, Celmara (Queensland Review, 2021)
The Great Barrier Reef is inscribed on the World Heritage List for its natural values, including an abundance of marine life and extraordinary aesthetic qualities. These and the enormous scale of the Reef make it unique and a place of ‘Outstanding Universal Value’. In the twentieth century, protection of the Great Barrier Reef shifted from limiting mechanical and physical impacts on coral reefs to managing agricultural runoff from adjacent mainland to minimise environmental impacts. By the early twenty-first century, it was apparent that threats to the Great Barrier Reef were no longer a local issue. Global warming, more frequent extreme weather events and increased ocean temperatures have destroyed vast swathes of coral reefs. Conservation scientists have begun trialling radical new methods of reseeding areas of bleached coral and creating more resilient coral species. The future of the Great Barrier Reef may depend on genetically engineered corals, and reefs that are seeded, weeded and cultured. This article asks whether the Great Barrier Reef can remain a natural World Heritage site or whether it might become World Heritage in Danger as its naturalness is questioned.